Role of ultrasound compared to age-related formulas for uncuffed endotracheal intubation in a pediatric population - Schramm, Christoph; Knop, Jana; Jensen, Katrin; Plaschke, Konstanze (Pediatric anesthesia, 2012)
Background: It is often difficult to determine the correct size of endotracheal tubes (ETT) needed for intubating pediatric patients. Therefore, we evaluated the role of ultrasound in pediatric patients to compare the correct size of an uncuffed (ETT) with the minimal transverse diameter of the subglottic airway (MTDSA) measured by ultrasound and with tube size predicted by different age-related formulas. Methods: A total of 50 pediatric patients ≤5 years were enrolled. As a standard, we defined the adequate ETT size with no audible leakage below a ventilation pressure of 15 mbar and with an audible leakage above 25 mbar. The maximum allowed difference between the prediction method result and the ETT that fit was defined as 0.3 mm. Ultrasound was performed before the intubation procedure; the intubating anesthesiologists were blinded to the results of the ultrasound measurement. Agreement between the two age-based formulas most commonly used at our department and MTDSA with the correct ETT size (standard) was analyzed using a Bland-Altman plot. Correlation and regression analyses were performed and the numbers of correct intubation trials recorded. Results: The frequency of bias ≤0.3 mm between each method and the correct ETT in the first attempt was <50% and the mean number of reintubations 1.6 ± 1.3. In contrast to age-related formulas, however, the ultrasonographically determined MTDSA was not significantly different from the correct ETT. MTDSA was highly associated with the outer diameter of the ETT (r = 0.869, R2 = 0.754). Conclusions: Measuring MTDSA by ultrasound facilitates selection of the appropriate ETT in pediatric patients and may reduce the number of reintubations.